Kesulitan Siswa Dalam Menyelesaikan Masalah Matematika Berdasarkan Langkah Polya - Amanda Putri Enlisia; Swasono Rahardjo; Sisworo Sisworo (Graduate School of Universitas Negeri Malang, 2020)
Abstract: The purpose of this study is to describe students' difficulties in mathematicals problem solving based on Polya's. The subjects in this study were 2 students of class VII. This type of research is descriptive qualitative. Data collection techniques through problem solving tests and interviews. The results of this study are (1) steps to understanding the problem that students have difficulty in understanding the sentences or terms contained in the problem, and students also have difficulty in finding keywords in the problem; (2) steps to devising the plan that students cannot make a mathematical model; (3) steps to carry out planning are students don’t understand the given problem and aren’t yet right in making mathematical models; (4) the step of looking back is that students don’t understand how to look back correctly and students are still lazy in checking the correctness of the answers.Abstrak: Tujuan penelitian ini adalah untuk mendeskripsikan kesulitan siswa dalam memecahkan masalah matematika berdasarkan langkah Polya. Subjek dalam penelitian ini adalah siswa kelas VII. Jenis penelitian yang digunakan adalah kualitatif deskriptif. Teknik pengumpulan data melalui tes pemecahan masalah dan wawancara. Hasil dari penelitian ini adalah (1) langkah memahami masalah yaitu siswa kesulitan dalam memahami kalimat atau istilah-istilah yang terdapat pada soal, dan siswa juga kesulitan dalam menemukan kata kunci pada soal; (2) langkah merencanakan masalah yaitu siswa belum dapat membuat model matematika; (3) langkah melaksanakan perencanaan adalah siswa kurang paham dengan masalah yang diberikan dan belum tepat dalam membuat model matematika; (4) langkah melihat kembali adalah siswa belum paham bagaimana cara melihat kembali dengan benar dan siswa masih malas dalam mengecek kebenaran jawaban.